Green Budgeting Review at Local Government: Case Study of Batu Government, Indonesia - Salahudin Salahudin; Mohamad Syahri; Tinuk Dwi Cahyani; Muhammad Firdaus (Journal of Government and Civil Society, 2025)
This study examines the implementation of green budgeting in Batu City in supporting sustainable development that includes environmental, social, and economic objectives. Many previous studies have explained green budgeting at the national level, focusing on budget policy alignment with sustainable development issues. Meanwhile, the focus of this research study is to review regional budgeting aimed at understanding local government budget policy alignment with green development issues in Batu City. Data were obtained through document analysis, in-depth interviews, and observations, and analyzed using NVivo to identify key themes, issue linkages, and policy priorities. Findings indicate that budgeting policies in Batu City have integrated strategic issues such as sustainable environment, agriculture, tourism, energy, and waste management. However, there is a gap between program/activity priorities and budget allocation, where important sectors such as sustainable plantations receive inadequate budget support. Public participation plays an important role in policy formulation, with primary attention to urban planning, traffic congestion, and environmentally friendly practices in the plantation sector. Waste management through TPS3R (Reduce, Reuse, Recycle) is recognized as a best practice, but budget inconsistencies indicate the need for better integration between policy vision and its realization. This research concludes that regional budgeting in Batu City has addressed several issues directly related to green development, including energy, waste management, tourism, agriculture, and sustainable environment. Nevertheless, there is a gap between planning and budget allocation, so that budget policies do not yet reflect a bias towards important issues related to the green economy. Therefore, public participation becomes the main key to realizing budget policies that support green development. The main recommendation of this research is that the Batu City government needs to seriously consider the consistency of planning and budget allocation so that budget policies align with important issues of green development. In addition, public participation needs to be increased and expanded to ensure that the budgeting process accommodates public issues related to green development.Â Penelitian ini mengkaji penerapan anggaran hijau di Kota Batu dalam mendukung pembangunan berkelanjutan yang mencakup tujuan lingkungan, sosial, dan ekonomi. Banyak penelitian terdahulu menjelaskan penganggaran hijau pada level nasional yang berfokus pada keberpihakan kebijakan anggaran terhadap isu-isu pembangunan yang berkelanjutan. Sementara fokus kajian penelitian ini, yaitu mereview penganggaran daerah yang bertujuan untuk mengetahui keberpihakan kebijakan anggaran pemerintah daerah terhadap isu-isu pembangunan hijau di Kota Batu. Data diperoleh melalui analisis dokumen, wawancara mendalam, dan observasi, serta dianalisis menggunakan NVivo untuk mengidentifikasi tema utama, keterkaitan isu, dan prioritas kebijakan. Temuan menunjukkan bahwa kebijakan penganggaran di Kota Batu telah mengintegrasikan isu strategis seperti lingkungan berkelanjutan, pertanian, pariwisata, energi, dan pengelolaan sampah. Namun, terdapat kesenjangan antara prioritas program/kegiatan dan alokasi anggaran, di mana sektor penting seperti perkebunan berkelanjutan mendapatkan dukungan anggaran yang kurang memadai. Partisipasi publik berperan penting dalam perumusan kebijakan, dengan perhatian utama pada perencanaan kota, kemacetan lalu lintas, dan praktik ramah lingkungan di sektor perkebunan. Pengelolaan sampah melalui TPS3R (Reduce, Reuse, Recycle) diakui sebagai praktik terbaik, tetapi inkonsistensi penganggaran menunjukkan perlunya integrasi lebih baik antara visi kebijakan dan realisasinya. Penelitian ini menyimpulakn bahwa penganggaran daerah di Kota Batu telah membahas beberapa isu yang berkaitan langsung dengan pembangunan hijau, di antaranya energi, pengolahan sampah, pariwisata, pertanian, dan lingkungan yang berkelanjutan. Kendati demikian, terdapat gap antara perencanaan dan alokasi anggaran sehingga kebijakan anggaran belum mencerminkan keberpihak terhadap isu-isu penting yang berkaitan dengan ekonomi hijau. Karena itu, partisipasi publik menjadi kunci utama untuk mewujudkan kebijakan anggaran pro pembangunan hijau. Rekomendasi utama penelitian ini, yaitu pemerintah Kota Batu perlu memperhatikan secara serius konsistensi perencanaan dan alokasi anggaran sehingga kebijakan anggaran selaras dengan isu-isu penting pembangunan hijau. Disamping itu, partisipasi publik perlu ditingkatkan dan diperlus untuk memastikan proses penganggaran mengakomodir isu-isu publik yang berkaitan dengan pembangunan hijau